Impact of pathological features of primary hepatocellular carcinoma on the outcomes of intrahepatic recurrence management: single center experience from Southern Taiwan. Issue 10 (October 2016) - Ali, Mahmoud Abdelwahab; Li, Wei-Feng; Wang, Jing-Houng; Lin, Chih-Che; Chen, Ying-Ju; Lin, Ting-Lung; Lin, Tsan-Shiun; Lu, Sheng-Nan; Wang, Chih-Chi; Chen, Chao-Long
Abstract: Background: Currently, there is no definitive management for hepatocellular carcinoma (HCC) intrahepatic recurrence (IHR) after primary resection (PR). The aim of this study was to analyze the outcomes of three modalities for patients who received curative PR and had IHR within the University of California San Francisco (UCSF) criteria. Methods: Between 2003 and 2010, patients with IHR after PR were treated with salvage liver transplantation (SLT), re-resection (RR) or local ablation (LA). Clinico-pathological features of primary tumor and recurrent HCC were analyzed to determine the risk factors that adversely affected overall survival (OS) and disease free survival (DFS). Results: The study included 130 patients with subgroups of SLT (n = 25), RR (n = 31) and LA (n = 74). The 5-year DFS and OS were 75%, 31% and 17% and 80%, 60% and 58% respectively for each subgroup. SLT had a significantly better DFS than other modalities (p < 0.001). There was no difference in OS. In multivariate analysis, two variables adversely affected DFS: microvascular invasion in PR and not treating patients with SLT. Conclusions: SLT provides better DFS for patients with IHR within the UCSF criteria. However, SLT failed to show the same advantage in OS.